Depression and Somatization in Refractory Lateral Epicondylitis - Eda GÜRÇAY,; Arif Uğur TAMKAN,; Özgür Zeliha KARAAHMET,; Yasemin TOMBAK,; Şükran GÜZEL,; Aytül ÇAKCI, (Archives of Rheumatology, 2019)
Objectives: This study aims to present two major psychological factors, namely depression and somatization, which may occur with high probability in patients with refractory lateral epicondylitis (LE). Patients and methods: This cross-sectional study included 36 patients (11 males, 25 females; mean age 42.6±8.09 years; range 26 to 60 years) diagnosed as refractory LE. Duration of symptoms was >6 months. Each patient completed the Beck Depression Inventory and the Symptom Checklist-90-Revised test evaluating psychosocial status and somatization, respectively. Results: Depression was found in 24 (66.6%) (moderate in 15 [41.7%] and mild in 9 [25%]) and somatization was found in 28 (77.8%) patients. Depression and somatization were significantly more common in females than males (p=0.02 and p=0.04, respectively). Conclusion: Depression and somatization may occur frequently in refractory LE patients, particularly in females. Both physical and psychological assessment tools should be incorporated into the clinical evaluation while psychological support should be included in the treatment of refractory LE.